An empirical investigation on China’s IPO first-day return after new regulation - He, Zhuopeng (2018)
The positive first-day return is recurring around the world and some research find China has the largest first-day gains. In order to solve this problem, China, in 2014, has promulgated a new regulation to limit the first-day maximum return to 44%. However, its effect is still unknown. Therefore, this paper studies 636 A-share IPOs issued in Shanghai Stock Exchanges and Shenzhen Stock Exchanges after the new regulation. It’s found that 1) after the new regulation, underpricing has become an effective and less risky way for issuers to maximise the initial return and the initial return mainly comes from the underpricing in the primary market; 2) the overpricing problem in the secondary market is basically not obvious and the secondary-market investors have become more rational. 3) the issue price, pre-listing PE ratio and ROE ratio, issue number and the listing waiting days are negatively related to the underpricing level, while the pre-listing asset-liability ratio, high-tech industry and the lottery rate have a positive relationship with the underpricing rate, compared to the insignificant variables of company size, issue cost and the underwriter’s reputation. 4) the closing price, ROE ratio, asset-liability ratio and lottery rate share a positive relationship with overpricing level, while the PE ratio is negatively related to the overpricing rate.